Storage stability of calcium-modified pandesal - King, Vanessa Mae E.; Dumelod, Benelyn Domingo (2001., 2001)
The storage stability of baked products is greatly restricted by the occurence of staling, microbiological spoilage and moisture content changes that result in less palatable, less desirable products and great economic losses on the part of the producer. This study aimed to determine the storage stability of pandesal fortified with calcium lactate under different temperatures and relative humidity conditions. Control and experimental pandesal samples were prepared an subjected to ensory evaluation, moisture content and water hydration capacity determination and compressibility tests. Calcium fortified pandesal under 28-32 degree C and 72-78% relative humidity had the highest overall acceptability rating (5.64), compression reading (1.76 mm/sec), water hydration capacity (0.7496), and lowest moisture content in the inner crumb (19.42%), outer crumb (17.99%) and crust (16.48) after four days; thus better resistance to staling. Control and experimental samples were also subjected to microbial evaluation, pH and water activity determination. Plate counts from all samples were well within the normal microbial load for baked products.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Bread; Enriched foods